2020
DOI: 10.3390/genes11020189
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Single-Step Genome-Wide Association Study for Growth Traits in Chinese Simmental Beef Cattle

Abstract: Improving the genetic process of growth traits is one of the major goals in the beef cattle industry, as it can increase meat production and reduce the cost of raising animals. Although several quantitative trait loci affecting growth traits in beef cattle have been identified, the genetic architecture of these economically important traits remains elusive. This study aims to map single nucleotide polymorphisms (SNPs) and genes associated with birth weight (BW), yearling weight (YW), average daily gain from bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Bärlocher et al illustrated TBC1D5 could promote the intracellular growth of L. pneumophila [ 63 ]. Notably, Zhuang et al reported TBC1D5 might play a special role in BW at 18 months of age in Chinese Simmental beef cattle [ 11 ]. Consistent with these findings, TBC1D5 was also identified as the functional gene for the bovine BW trait in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bärlocher et al illustrated TBC1D5 could promote the intracellular growth of L. pneumophila [ 63 ]. Notably, Zhuang et al reported TBC1D5 might play a special role in BW at 18 months of age in Chinese Simmental beef cattle [ 11 ]. Consistent with these findings, TBC1D5 was also identified as the functional gene for the bovine BW trait in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Buzanskas et al revealed four SNPs significantly associated with the BW trait in Canchim beef cattle [ 10 ]. Zhuang et al performed the weighted single-step GWAS in 744 Chinese Simmental beef cattle with 770K BovineHD SNP BeadChip, concluding TBC1D5 and MYH10 were associated with birth weight at the age of 18 months and YW [ 11 ], respectively, of which MYH10 was also identified to be related to chicken growth traits [ 12 ]. Amounts of candidate genes and significant SNPs relevant to the BW trait have been identified and submitted to Cattle Quantitative Trait Locus Database (Cattle QTLdb) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…NCAPG was also reported to be in linkage disequilibrium with the average daily gain (ADG) in cattle [ 89 ]. Candidate genes for muscle development and growth identified in Simmental beef cattle include MYH10 (associated with yearling weight), RLF (associated with ADG from birth to yearling), SQOR and ARHGAP31 (associated with body weight at the age of 18 months), and TBCB (associated with birth weight) [ 90 ]. TBCB was identified as a candidate gene affecting meat quality in pigs because it is associated with actin and cytoskeleton filament development [ 91 ].…”
Section: Candidate Genes Affecting Muscle Development In Cattlementioning
confidence: 99%
“…All these candidate genes for Ab response to ND have not been heretofore directly associated with immune response in poultry (Adhikari and Davie, 2018;Elbeltagy et al, 2019). Some of these genes are new genes in the chicken and have mostly been discussed in other species (Zhou et al, 2014;Fleming et al, 2016;Zhuang et al, 2020). Further examination is therefore required to prove these novel genes as putative genes for Ab response to ND in chicken.…”
Section: Possible Causal Variant For Antibody Response To Newcastle Disease In Indigenous Chicken In Rwandamentioning
confidence: 99%